The Population of Bacteria and CO2 Release on Process of Composting Manure and Swamp Grass - Diana Utama; Nuni Gofar; Fitri Siti Nurul Aidil (Program Pascasarjana Universitas Sriwijaya, 2017)
This study aimed to analyze the bacteria population, the release of CO2, pH and organic-C and total-N in the process of compost made from manure and swamp grass. Treatment level consist of 100% manure (K100), 50% of manure + 50% swamp grass (K50R50), 25% of manure + 75% swamp grass (K25R75), and 10% of manure + 90% swamp grass (K10R90). The result of this study indicated the dynamic of different bacteria population on different composting materials by increasing of the composting time. The release of CO2 decrease on all treatment levels by increasing of the composting time. The pH value increased at all levels of treatment, except the composition of 100% manure. The best composition obtained by mixing of 10% manure and 90% swamp grass.Keywords: CO2 release, compost, manure, population, swamp grass.